Examining Treatment Outcomes with Erlotinib in Patients with Advanced Non–Small Cell Lung Cancer Whose Tumors Harbor Uncommon EGFR Mutations. Issue 4 (April 2016) - Klughammer, Barbara; Brugger, Wolfram; Cappuzzo, Federico; Ciuleanu, Tudor; Mok, Tony; Reck, Martin; Tan, Eng Huat; Delmar, Paul; Klingelschmitt, Gaëlle; Yin, Anny‐Yue; Spleiss, Olivia; Wu, Lin; et al.
ABSTRACT : Introduction: : Exon 19 deletions and the exon 21 L858R mutation of the epidermal growth factor receptor gene ( EGFR ) predict activity of EGFR tyrosine kinase inhibitors, including erlotinib; however, the ability of less common EGFR mutations to predict efficacy of erlotinib is unclear. Methods: : The efficacy of erlotinib in individual patients with rare EGFR mutations from the MERIT, SATURN, TITAN, TRUST, ATLAS, BeTa, and FASTACT‐2 trials was analyzed and compared with data from the literature. Results: : In the patients tested for biomarkers, the frequency of rare mutations identified here ranged from 1.7% (eight of 467) in the SATURN study to 7.4% (27 of 364) in ATLAS. Some rare mutations were associated with greater clinical benefit from EGFR tyrosine kinase inhibitor therapy or improved prognosis independent of treatment, whereas others appeared to have a poorer prognosis. In particular, exon 18 G719 mutations, exon 19 K757R and E746G mutations, the exon 20 S768I mutation, and the exon 21 G836S mutation appeared to confer a good outcome with erlotinib treatment, whereas exon 18 S720I showed a particularly poor outcome. Owing to the small number of patients with each mutation, however, it is difficult to confirm whether these rare mutations do indeed confer sensitivity or resistance to erlotinib. Conclusions: : Erlotinib can have different efficacy depending on the specific EGFR mutation. More research is needed to create a central database such as the My Cancer Genome database of rare mutations to definitively confirm whether these mutations are activating, resistant, or neutral.